Pro-environmentalists behavioural assessment towards energy conservation among Malaysian university students - Mohamad Kawi, Nur Farisha Husna; Ishak, Mohd Hafizal (Penerbit UTHM, 2021)
Pro-environmental are the key players in promoting environmental behaviour to the public. This behaviour covers several broader aspects, especially including energy-used behaviour. However, some career pro-environments ignore their behaviour towards the environment which has affected the public expectation towards them especially in terms of energy conservation. The past researcher believed that pro-environmental literacy should be taught from young ages, at least before they become teenagers or before they get a job placement in future. Therefore, this research was conducted on selected university students in Malaysia. Their knowledge and readiness for pro-environmental behaviour towards energy conservation are really important to ensure the sustainability of development, organization, and workplace. The objectives of this research are to identify the key drivers and pro-environmental barriers among students and to analyse the level of the influences of key drivers and barriers to pro-environmental behaviour levels. The quantitative method was used through the questionnaire with 102 sheets distributed to the students. Descriptive statistic and correlation analysis were used for analysing the data. Each student possesses all six of these categories. But what differentiates them is the level of their application in each category to the dependent variables. The results of the study found that the two categories (activist and avoider) are not too burdensome about energy-used behaviour compared to environmental behaviour. Furthermore, this study found that avoider is the least burdensome category of any behaviour while it is included in the PEB category.